RISIKO KARBON DAN BIAYA EKUITAS: APAKAH TATA KELOLA PERUSAHAAN BERPERAN? - Denisa Nasywa Inaya; Dini Rosdini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effect of carbon intensity on the cost of equity with corporate governance as a moderating variable in companies listed on the Indonesia Stock Exchange during 2023–2025. The sample in this study was obtained using a purposive sampling method, and the analysis technique applied is panel data regression, which includes descriptive statistics, model selection tests, classical assumption tests, and hypothesis testing. The data used is an unbalanced panel with a total of 320 observations from 109 companies. The results show that carbon intensity has a positive and significant effect on the cost of equity, while corporate governance, both directly and as a moderating variable, has no significant effect on the cost of equity or on the relationship between carbon intensity and the cost of equity. Regarding the control variables, ROA has a significant negative effect, leverage has no significant effect, and firm size has a significant positive effect on the cost of equity. Simultaneously, all independent and control variables have a significant effect on the cost of equity.